Sleep duration regularity, but not sleep duration, is associated with microvascular function in college students. Issue 2 (9th September 2020) - Hoopes, Elissa K; Berube, Felicia R; D'Agata, Michele N; Patterson, Freda; Farquhar, William B; Edwards, David G; Witman, Melissa A H
Abstract: Study Objectives: Vascular dysfunction is a hypothesized mechanism linking poor sleep habits to an increased incidence of cardiovascular diseases (CVDs). However, the vascular profile associated with free-living sleep duration and sleep regularity has not been well elucidated, particularly in young adults. Thus, this study aimed to evaluate the associations between mean sleep duration, regularity in sleep duration, and peripheral vascular function in young adult college students. Methods: Fifty-one healthy undergraduate students (20 ± 1 years) completed 14 days of 24-hour wrist actigraphy and subsequent vascular assessments. Macrovascular function was measured using brachial artery flow-mediated dilation (FMD) while microvascular function was measured via passive leg movement (PLM). Results: Mean sleep duration was unrelated to FMD and PLM. Conversely, more irregular sleep duration (14-day sleep duration standard deviation [SD]) was unfavorably associated with all three measures of PLM-induced hyperemia (peak leg blood flow [LBF], p = 0.01; change in LBF from baseline to peak, p < 0.01; LBF area under the curve, p < 0.01), and remained significant in regression models which adjusted for sex, body mass index, blood pressure, physical activity, alcohol and caffeine consumption, and sleep duration (all p < 0.05). When using a median split to dichotomize "low" and "high" sleep duration SD groups, those demonstrating high variability in sleep duration exhibited ~45% lower PLM responses compared with those demonstrating low variability. Conclusions: Irregular sleep duration is associated with poorer microvascular function as early as young adulthood. These findings support the growing body of evidence that irregular sleep patterns may be an independent and modifiable risk factor for CVD.